RANCANG BANGUN SISTEM MANAJEMEN DATA MENGGUNAKAN QR CODE BERBASIS WEB PADA PT DENSO MANUFACTURING INDONESIA - Raynor Hayat; Kuswandi Kuswandi (JURNAL LENTERA ICT, 2025)
This research aims to design and build a web-based data management system using QR Code technology to address production machine data management issues at PT Denso Manufacturing Indonesia Cikarang Baru. The current system still relies on manual methods using Microsoft Excel and physical documents, resulting in delayed information access, the risk of input errors, and the difficulty of real-time data tracking. This research employed a Research and Development (R&D) method, including literature review, observation, and interviews to identify system requirements. The system was designed using Unified Modeling Language (UML), which includes Use Case diagrams, Activity diagrams, sequence diagrams, and class diagrams. The database was optimized through normalization and Entity Relationship Diagrams (ERDs). The resulting web-based system allows Admins and Users to manage machine data through features such as registration, login, data addition, QR Code scanning, and data updates, with access controlled based on user roles. This system has successfully improved operational efficiency, reduced machine downtime, and supported the digitalization of work processes at PT Denso Manufacturing Indonesia, while positively contributing to the company's productivity and digital transformation.